Karakteristik kasus pada Visum et Repertum di RSUP dr. Soeradji Tirtonegoro Klaten 2014-2016 - idha arfianti wiraagni; Edy Widihartono (Pharmaciana, 2016)
Since the opening of forensic services at RSUP dr. Soeradji Tirtonegoro Klaten since 2014, many forensic cases were handled. Based on the type of case, in the death cases, there are traffic accidents, crime, and other deaths. While in life cases, there are sexual violence, physical violence, and psychiatry. Research on basic characteristic patients’ are very important to do, especially for the police, government, hospital, and community. The purpose of this study was to determine the basic characteristic patients’ of Visum et Repertum in RSUP dr. Soeradji Tirtonegoro Klaten 2014-2016. This research was a cross-sectional study, with a total sampling method. The data were taken from Visum et Repertum during    2014 - March 2016. There were 242 life cases (124 women, 118 men), and 23 death cases (6 women, 17 men). Most patients were productive age (22-40 years old), with 33.5% life cases and 30.4% death cases. The highest number of life cases was physical abuse (109 cases; 45%), then all of death cases was accident. The highest profession of patients were students (30.6% in life cases), while in the death cases were private (43.5%). Head trauma was the most common injury in patients (45.9% life cases and 82.6% death cases). Most of the perpetrators were unknown people (77.7% life cases, as well as 82.6% of death cases). From both cases, the patients were from productive age, distribution of fatal wound was in the head, and the prepetators were unknown. These data are very important in educational process of society.